Improving The Ability Of Students Of Class Iii A Elementary School 0804 Botung In Answering The Contents Of Fairytale Using Indonesian Language Good Through Guidance And Training T.P 2020/2021 - Lanniari Nasution (STKIP Rokania Pasir Pangaraian, 2021)
The purpose of this study was to improve Indonesian language learning outcomes through Guidance and Training in class IIIA SD Negeri 0804 Botung in the 2020/2021 academic year. Observations of learning outcomes and observations of the learning process can be concluded that learning with the application of the Guidance and Exercise method can improve Indonesian language learning outcomes in class III Semester 1 SD Negeri 0804 Botung for the 2020/2021 academic year. It is proven that the average value of the class in the pre-cycle is 62.67 with 37% learning completeness in the first cycle to 75 (70%) and in the second cycle it becomes 85.33 with 87% complete. Thus, the hypothesis proposed by the researcher has been proven true